The Saving for Every Child Program in Israel: an overview of a universal asset-building policy. Issue 1 (2nd January 2019) - Grinstein-Weiss, Michal; Kondratjeva, Olga; Roll, Stephen P.; Pinto, Ofir; Gottlieb, Daniel
ABSTRACT: In 2017, the Israeli government implemented a universal child development account programme – the Saving for Every Child Program (SECP) – which establishes a personal savings account for every Israeli child and provides monthly deposits until the child turns 18. The SECP has the potential to provide substantial assets when children reach adulthood, but the benefits depend on parents' investment choices. The unique programme's nature presents opportunities to learn from its implementation. This paper provides a comprehensive overview of the SECP, its legislative history, early findings from its implementation, and recommendations that may improve programme participation and outcomes across population groups.